Jumping on the Bandwagon: The Role of Voters' Social Class in Poll Effects in the Context of the 2021 German Federal Election - Fabienne Unkelbach; Melvin John; Vera Vogel (Politische Vierteljahresschrift, 2022)
Published findings of opinion polls are an important part of the political coverage before elections. Thus, researchers have long investigated whether the perceived popularity of political parties can lead to even more voters following this majority. However, empirical findings on this so-called political bandwagon effect are mixed. In the present paper, we integrate theories from political science and social psychology to explain these inconsistencies through social class as a~potential moderating variable. Based on previous findings regarding consumer decisions, we hypothesized that bandwagon effects are greater among voters with lower social class. To investigate this hypothesis, we combined data from the German Longitudinal Election Study (GLES) Rolling Cross-Section 2021, which was collected over the 55~days before the 2021 German federal election, with the results of published preelection polls. Using separate multilevel models for each of the parties, we found no evidence for bandwagon effects. Only for the Social Democratic Party were poll results related to voting intentions assessed on the following day, suggesting that polls might have contributed to the party's electoral success. However, there was no evidence for a~moderation of bandwagon effects by voters' social class. Accordingly, we could not resolve the mixed findings in this field of research. Our results point to important open questions in research on bandwagon effects in multiparty systems as well as on effects of social class in Germany.
Keywords: 320; Mass media; Social influence; Social psychology; Voting intention; Rolling cross-section study; Massenmedien; Sozialer Einfluss; Sozialpsychologie; Wahlabsicht; Rolling Cross-Section Wahlkampfstudie